2013
DOI: 10.3390/nu5061937
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Selenoprotein P and Glucose Metabolism in Experimental Studies

Abstract: Selenium is an essential trace element in the diet of mammals which is important for many physiological functions. However, a number of epidemiological studies have suggested that high selenium status is a possible risk factor for the development of type 2 diabetes, although they cannot distinguish between cause and effect. Selenoprotein P (Sepp1) is central to selenium homeostasis and widely expressed in the organism. Here we review the interaction between Sepp1 and glucose metabolism with an emphasis on expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 59 publications
0
38
0
3
Order By: Relevance
“…Unexpectedly, recent human trials and animal studies have suggested that long-term Se intake increased the risk of insulin resistance and type 2 diabetes (Bleys et al, 2007;Stranges et al, 2011). Recently, a number of studies have suggested that selenoproteins, such as GPX, SelS and SelP, were also closely associated with diabetes or metabolic syndrome in mammals (Labunskyy et al, 2011;Mao and Teng, 2013;Misu et al, 2010;Seale et al, 2012;Steinbrenner, 2013). No matter the insulin-like effect or the increasing the risk of insulin resistance and type 2 diabetes, at least it is indicated that selenoproteins as the carrier of Se may be related to the glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…Unexpectedly, recent human trials and animal studies have suggested that long-term Se intake increased the risk of insulin resistance and type 2 diabetes (Bleys et al, 2007;Stranges et al, 2011). Recently, a number of studies have suggested that selenoproteins, such as GPX, SelS and SelP, were also closely associated with diabetes or metabolic syndrome in mammals (Labunskyy et al, 2011;Mao and Teng, 2013;Misu et al, 2010;Seale et al, 2012;Steinbrenner, 2013). No matter the insulin-like effect or the increasing the risk of insulin resistance and type 2 diabetes, at least it is indicated that selenoproteins as the carrier of Se may be related to the glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…[32] However, some studies have demonstrated a negative correlation between SeP level, gene expression, obesity and IR. [31] In the present study we performed a correlation analysis between SeP and anthropometric parameters, and found negative correlations between SeP and waist circumference in the patient group, and also between SeP and BMI and the percentage of adipose tissue in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[30] In a review article written by Mao and Teng, the authors indicated that in a case of normal insulin sensitivity, insulin will suppress release of SeP from the liver, while in the case of IR, this feedback mechanism fails to function and an increase in SeP level occurs, which may induce an increase in blood glucose level. [31] In another study in which 100 patients with varying glucose tolerance levels were evaluated, a higher plasma SeP concentration was detected in cases with normal glucose tolerance relative to cases with type 2 DM or prediabetes, and enhanced plasma SeP levels were found to be positively correlated with BMI and IR. [9] In our study, higher IR was detected in patients with PCOS, though not statistically significantly different, and mean plasma SeP level was lower than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has chemopreventive, anti-inflammatory, antiviral properties and is related in enhancing immunity (Rayman, 2012;Steinbrenner et al, 2013). The health-related properties of Se include but are not limited to protection against cancer, proper function of thyroid gland, and protection against cardiovascular and muscle disorders (Mao and Teng, 2013;Rocourt and Cheng, 2013). Se becomes cotranslationally incorporated into the polypeptide chain as part of the amino-acid selenocysteine (SeCys).…”
Section: Introductionmentioning
confidence: 99%